2014
DOI: 10.1002/anie.201309074
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Palladium‐Catalyzed Allylic Alkylation Using Dialkylzinc Reagents: A Remarkable Ligand Effect

Abstract: A serendipitously discovered palladium-catalyzed asymmetric allylic alkylation reaction with diorganozinc reagents, which displays broad functional group compatibility, is reported. This novel transformation hinges on a remarkable ligand effect which overrides the standard "umpolung" reactivity of allyl-palladium intermediates in the presence of dialkylzincs. Owing to its mild conditions, enantioselective allylic alkylations of racemic allylic electrophiles are possible in the presence of sensitive functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…Our study data indicate that the luminescence intensity of ZIF-90 is highly sensitive to Cd 2+ and Cu 2+ ions owing to the interaction with imidazole nitrogen sites of organic ligands. The CrO 4 2− anions and small molecules such as acetone have the competition for absorption with ICA. The luminescence intensity of desolvated ZIF-90 increases proportionally with the concentration of Cd 2+ but decreases proportionally with the concentration of Cu 2+ , and decreases with the increase of CrO 4 2− anions and acetone in the emulsions of ZIF-90a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study data indicate that the luminescence intensity of ZIF-90 is highly sensitive to Cd 2+ and Cu 2+ ions owing to the interaction with imidazole nitrogen sites of organic ligands. The CrO 4 2− anions and small molecules such as acetone have the competition for absorption with ICA. The luminescence intensity of desolvated ZIF-90 increases proportionally with the concentration of Cd 2+ but decreases proportionally with the concentration of Cu 2+ , and decreases with the increase of CrO 4 2− anions and acetone in the emulsions of ZIF-90a.…”
Section: Discussionmentioning
confidence: 99%
“…The luminescence of ZIF-90a was gradually quenched with the increase of CrO 4 2− concentration (Fig. 7).…”
Section: Sensing Of Anions and Organic Small Moleculesmentioning
confidence: 94%
See 1 more Smart Citation
“…of 21-25, respectively, with no further optimization of the reaction conditions. We found that vinylboronic acids can also be used as nucleophiles under the same reaction conditions (entries [25][26][27] to give 26-28, respectively. Here, good yields and high levels of enantioselectivity were observed when the reaction time was extended from one to four hours.…”
mentioning
confidence: 92%
“…Pd-catalysed processes that convert a racemic mixture of starting materials into a new single-enantiomer product are commonly referred to as dynamic kinetic asymmetric transformations (DYKATs), as originally developed by Trost and co-workers 24 . DYKATs can now be used with a wide variety of stabilized nucleophiles and an array of metal catalysts 24 and several non-stabilized sp 3 -hybridized nucleophiles can now be used in certain related procedures [25][26][27][28] .…”
mentioning
confidence: 99%